Factors Influencing Wellness/Well-Being among Childrenin from Mothers’ Perspectives - al abidi, Suzan; Al-Khaza’leh, Mohammad Salman; taani, Osama hekmat (Opción)
This ethnographic research was conducted in to investigate factors influencing wellness/well-being among children from their mothers’ perspectives. Data were collected via semi-structured interviews with seven Muslim mothers from different countries, observation, and field notes. The ecological model and Hettler’s definition of wellness were used as frameworks for understanding Muslim mothers’ experiences. Using thematic analysis, themes emerged as research question: 1) factors impacting wellness/well-being (discrimination, cultural friction, apprehension and fear, lack of awareness of Islam, and misalignment of organizational processes. The study identifies its limitations and implications for future research.